Population geography social justice for a sustainable world - Hazen, Helen 1975-; Alberts, Heike C.; Zaniewski, Kazimierz J. (Abingdon, Oxon Routledge, 2024)
Population Geography: Social Justice for a Sustainable World surveys the ways in which geographic approaches may be applied to population issues, exploring how human populations are embedded in natural and social environments. It encourages students to evaluate population issues critically, given that population topics are at the heart of many of today's most contentious subjects. Through introducing students to different lenses of analysis (ecological, economic and social equity), the authors ask students to consider how different perspectives can lead to different conclusions on the same issue. Identifying and tackling today's population problems therefore requires an understanding of these diverging, and sometimes conflicting, perspectives. The text will cover all the key background information critical to any book on population geography (population size, distribution, and composition; fertility, mortality, and migration; population and resources), but will also push students to think critically about the materials they have covered using these twin lenses of sustainability and social justice. In this way, students move beyond simple fact learning towards higher-level skills such as analysis, synthesis, and evaluation of materials. This textbook will be a valuable resource for students of human geography, population geography, demography and diaspora studies"--
Contents: Introduction to population geography - - Demographic data, visualization, and interpretation - - Population distribution and composition - - Population growth and change - - Population and resources - - Fertility measures and patterns - - Ethical issues in fertility - - Mortality and morbidity - - Emerging trends in population health - - Migration patterns and theories - - Social justice issues in migration - - Sustainability and social justice in population issues.
Includes bibliographical references and index.
Keywords: Population geography; Social justice; Sustainable development